A molecular toolkit for heterologous protein secretion across Bacteroides species - Yu-Hsuan Yeh; Vince W. Kelly; Rahman Rahman Pour; Shannon J. Sirk (Nature Communications)
Abstract Bacteroides species are abundant, prevalent, and stable members of the human gut microbiota, making them a promising chassis for developing long-term interventions for chronic diseases. Engineering Bacteroides as in situ bio-factories, however, requires efficient protein secretion tools, which are currently lacking. Here, we systematically investigate methods to enable heterologous protein secretion in Bacteroides. We identify a collection of secretion carriers that can export functional proteins across multiple Bacteroides species at high titers. To understand the mechanistic drivers of Bacteroides secretion, we characterize signal peptide sequence features, post-secretion extracellular fate, and the size limit of protein cargo. To increase titers and enable flexible control of protein secretion, we develop a strong, self-contained, inducible expression circuit. Finally, we validate the functionality of our secretion carriers in vivo in a mouse model. This toolkit promises to enable expanded development of long-term living therapeutic interventions for chronic gastrointestinal disease.